Evaluation of anti-cancer function in natural killer cells generated from rat hematopoietic stem cells / Alireza Pirahmadian - Alireza , Pirahmadian (2020)
Natural killer cells (NK) cells are lymphocytes and they are the most important key constituent of mammalian immune system against cancer tumour cells. The genome of NK cells is categorically divided to inhibitory and activator genes that code ligands on the surface of NK cells. Indeed, these ligands are cancer tumour cells destroyer arms of the NK cells. On the other hand, hematopoietic stem cells (HSCs) are the origin of all blood cells, derives from BM and mature to immune cells. NK cells cannot defeat CTCs on their own. The main reason is their population (numbers are low), they cannot derive from HSCs as fast as CTCs division rate, and that is why external treatments have to be used to treat cancer. This project, designed to promote and give potency to immune system against CTCs without relying on external treatments. To obtain this goal, three specific genes of NK cells, cloned in BMHSCs and differentiated the stem cells to NK cells. The success of the colonization has been examined by western blot and flow cytometry and in term of functionality of newly generated NK cells the cytotoxicity has been examined by MTT assay and Live and Dead assay and the apoptosis ability of newly generated NK cells have been examined by RARP Cleavage and Caspase 3/7 assay. The results and data approve that the generated NK cells from BMHSCs are able to destroy cancer cells.